2013
DOI: 10.1021/nn4019009
|View full text |Cite
|
Sign up to set email alerts
|

Strained Lattice with Persistent Atomic Order in Pt3Fe2 Intermetallic Core–Shell Nanocatalysts

Abstract: Fine-tuning nanocatalysts to enhance their catalytic activity and durability is crucial to commercialize proton exchange membrane fuel cells. The structural ordering and time evolution of ordered Pt3Fe2 intermetallic core-shell nanocatalysts for the oxygen reduction reaction that exhibit increased mass activity (228%) and an enhanced catalytic activity (155%) compared to Pt/C has been quantified using aberration-corrected scanning transmission electron microscopy. These catalysts were found to exhibit a static… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
96
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 32 publications
2
96
1
Order By: Relevance
“…[287][288][289][290][291][292][293][294][295][296][297] In this section, various catalytic reactions by CSNs 298 are described, such as hydrogenation reactions, oxidation reactions, cross-coupling reactions, tandem deprotection-Knoevenagel and Henry reactions, aerobic oxidative esterifications and synthesis of bulk chemicals (e.g., adipic acid), etc. [287][288][289][290][291][292][293][294][295][296][297] In this section, various catalytic reactions by CSNs 298 are described, such as hydrogenation reactions, oxidation reactions, cross-coupling reactions, tandem deprotection-Knoevenagel and Henry reactions, aerobic oxidative esterifications and synthesis of bulk chemicals (e.g., adipic acid), etc.…”
Section: Applications Of Core-shell Nanoparticles In Catalysismentioning
confidence: 99%
“…[287][288][289][290][291][292][293][294][295][296][297] In this section, various catalytic reactions by CSNs 298 are described, such as hydrogenation reactions, oxidation reactions, cross-coupling reactions, tandem deprotection-Knoevenagel and Henry reactions, aerobic oxidative esterifications and synthesis of bulk chemicals (e.g., adipic acid), etc. [287][288][289][290][291][292][293][294][295][296][297] In this section, various catalytic reactions by CSNs 298 are described, such as hydrogenation reactions, oxidation reactions, cross-coupling reactions, tandem deprotection-Knoevenagel and Henry reactions, aerobic oxidative esterifications and synthesis of bulk chemicals (e.g., adipic acid), etc.…”
Section: Applications Of Core-shell Nanoparticles In Catalysismentioning
confidence: 99%
“…However, the stability and activity of the MPt catalysts can be dramatically improved once the M and Pt are in an ordered intermetallic L1 0 structure. 168,192,411,412 Taking the FePt NPs as an example, the L1 0 -FePt is chemically more stable and catalytically more active for the ORR than the A1-FePt in acidic environment due to the unique intermetallic structure. 168 The key here is to obtain fully ordered L1 0 -FePt NPs.…”
Section: Magnetic Nanoparticles As Catalysts In Electrochemical Reactmentioning
confidence: 99%
“…Oxygen reduction electrocatalysts are known to play a crucial role on fuel cells performance, being the fundamental studies on the subject still required to overcome these barriers 3,4 . By alloying Pt with other non-noble metals, it is possible to produce cheaper electrocatalysts with novel properties for the oxygen reduction reaction (ORR) due to lattice compression 5,6 and/or modified electronic properties 7,8 . Thus, several studies have shown that binary Pt-M (M=Cr, Mn, Fe, Co, Ni, Cu, V, Ti) nanocrystals (NCs) greatly enhanced the kinetics of the ORR in comparison with standard Pt catalysts [9][10][11] .…”
mentioning
confidence: 99%